Effects of COVID-19 pandemic on cardiac surgery and practice. Did we hit the mark: strategy or casuality?. (14th October 2021) - Di Gaetano, M; Minotti, A S; Usai, F; Morini, E; Contristano, M L
Abstract: Background: COVID-19 pandemic is having a collateral health effect on delivery of surgical therapies and reports from management and maintaining surgical care are little. Purpose: Investigate the impact of COVID-19 in our cardiac surgical ward and practice by scoping review of the last two years of activity, between 1st March 2019 and 28th February 2021. Methods: Our Hospital is a private institution accredited with the National Health Service with a global volume load of 750 cardiac cases per year. We analized the pre-pandemic and the ongoing pandemic period on volume activity, the capacity of satisfying the needs of cardiosurgical patient and the mortality rate. Results: We observed a minimal cardiac surgery caseload decline of 14.8%, probably due to environmental factor, the absence of E.D. in our institute, the rapid re-organization pathways, the hospital surveillance, the supply of personal protective equipment, the informative measures to improve patient and personnel welfare. In order to enhance the pshycological impact of this devastating event, we invited all the health workers to fill a questionnaire regarding concerns and worries about the risk of transmitting the infection to their families or to aquire it themselves. Conclusion: During this devastating pandemic the rapid response in re-organization pathways and hospital surveillance allowed us to preserve the cardiac surgery volume of life-saving and non deferrable cases. Funding Acknowledgement: Type of funding sources: None.